STUDI PERBANDINGAN KINERJA PORTOFOLIO SAHAM BERDASARKAN KAPITALISASI PASAR DI BURSA EFEK INDONESIA DENGAN RISK ADJUSTED RETURN - Wahyuni, Komang Tri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
The debate about the formation of a portfolio based on market capitalization (firm size) is common in several empirical studies. The purpose of this research is to analyze the performance of stock portfolio based on market capitalization at Indonesian Stock Exchange during period January â€“ December 2017. These reaserch is also to test the comparison of stock portfolio performance between big, middle and small market capitalizations. Performance of stock portfolio based on market capitalization is measured by Risk Adjusted Return (index of Sharpe, Treynor and Jensen), and to test the comparison of stock portfolio performance between big, middle and small market capitalizations is tested by using statistic analysis independent sample t-test. The result of these research are stock portfolio of small market capitalization (small caps) is outperform than big caps and middle caps measured by index Sharpe, but big caps outperform if measured by index Treynor and middle caps by index Jensen at Indonesia Stock Exchange during periode 2017. T-test analysis of stock portfolio based on market capitalization is founding that stock portfolio big caps vs middle caps, big caps vs small caps and middle caps vs small caps are not difference signiï€cantly